Enhanced ionization of acetylene in intense laser pulses is due to energy upshift and field coupling of multiple orbitals - Erattupuzha, Sonia; Covington, C. L.; Russakoff, A.; Lotstedt, E.; Larimian, S.; Hanus, V.; Schoeffler, M.; Bubin, Sergiy; Koch, M.; Gräfe, Stefanie; Baltuska, Andrius; Xie, Xinhua; et al. (Journal of Physics: Conference Series, 2017)
We describe a new enhanced ionization mechanism for polyatomic molecules. It works via a significant energy up-shift of valence orbitals for stretched bonds and a strong concomitant increase in the coupling between multiple molecular orbitals.
CRIS-Team Scopus Importer:2023-04-20